2012
DOI: 10.1038/nm.2728
|View full text |Cite
|
Sign up to set email alerts
|

Adora2b-elicited Per2 stabilization promotes a HIF-dependent metabolic switch crucial for myocardial adaptation to ischemia

Abstract: Studies of metabolic adaptation during environmental stress have broad applications to human disease. Adenosine signaling has been implicated in cardiac adaptation to limited oxygen availability. Serendipitously, a wide search for adenosine receptor A2b (Adora2b)-elicited cardio-adaptive responses identified the circadian rhythm protein period2 (Per2). Subsequent pharmacologic and genetic studies confirmed Adora2b-dependent stabilization of Per2 during myocardial ischemia. Functional studies of myocardial isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

35
397
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(452 citation statements)
references
References 60 publications
35
397
7
1
Order By: Relevance
“…Thus, HIF-1 activates multiple protective pathways in response to ischemia. Direct IPC of the heart was shown to be dependent upon functional interaction of HIF-1α with the circadian rhythm protein PER2 (32), and further studies are required to determine whether PER2 is required for HIF-1− dependent induction of IL-10 in response to [3 × I 5 R 5 ] fem . Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, HIF-1 activates multiple protective pathways in response to ischemia. Direct IPC of the heart was shown to be dependent upon functional interaction of HIF-1α with the circadian rhythm protein PER2 (32), and further studies are required to determine whether PER2 is required for HIF-1− dependent induction of IL-10 in response to [3 × I 5 R 5 ] fem . Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had implicated CD73-dependent generation of extracellular adenosine and concomitant adenosine signaling in tissue protection during conditions of acute tissue injury, such as AKI, [21][22][23][24][25][26] hepatic 10,20,27 or intestinal 17,18,28 ischemia, or myocardial infarction. 10,[29][30][31][32] In contrast, the functional role of extracellular adenosine generation and signaling during chronic disease states is less clear. For example, extracellular adenosine generation and signaling appears to be protective during the acute phase of lung injury, but has been implicated in promoting a fibrotic response during chronic forms of lung disease.…”
mentioning
confidence: 99%
“…In a previous study, per2-mutant mice showed a failure to stabilize HIF1a [10]. Per2 suppressed Clock-Bmal1-and Clock-Bmal2-dependent transactivation of the Pai1 promoter in vitro [11].…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, it is conceivable that VEGF mRNA expression by neutrophils infiltrating in the wound tissue may be under the influence of circadian gene per2 oscillation. On the other hand, per2-mutant mice develop larger infarct sizes by myocardial ischemia compared with wild-type mice, and lose the cardioprotection conferred by ischemic preconditioning [10]. This impairment is most likely caused by a failure to stabilize hypoxia-inducible factor1alpha (HIF1a) [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation